KEEFEKTIFAN KOLABORASI MODEL PEMBELAJARAN AIR DENGAN CRH BERBANTUAN VIDEO PEMBELAJARAN TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Wulandari, Nur Indri; Mardhiyana, Dewi (Kadikma, 2022)
This study aims to: (1) determine the average ability to understand mathematical concepts of students who are taught using the collaborative learning model AIR (Auditory, Intellectual, Repetition) with CRH (Course Review Horay) assisted by video learning is better than the average understanding of mathematical concepts students who are taught using conventional learning models, (2) knowing the average mathematical concept understanding ability of students who use the AIR (Auditory, Intellectual, Repetition) collaborative learning model with CRH (Course Review Horay) assisted by learning videos to achieve the Minimum Completeness Criteria (KKM). This research is a quantitative research with experimental method. The population of this study were all eighth grade students of MTs Nurul Huda Banyuputih in the even semester 2021/2022 academic year. Data collection was carried out using the test method. The data obtained were analyzed by t test and Z test. The results showed: (1) the average mathematical concept understanding ability of students who are taught using the AIR collaboration model with CRH assisted by video learning is better than the average understanding of mathematical concepts of students who are taught using the model conventional learning, (2) the proportion of students taught using the AIR collaboration model with CRH assisted learning video gets a score of more than 75%.